Potebnia’s Hermeneutic Paradigm as a Process of Perception – Understanding – Interpretation - Левченко, Наталія Микитівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to the study of O. Potebnia’s hermeneutic ideas. It is pointed out that scientific research of O. Potebnia, the founder of Kharkiv philological school, is based on W. Humboldt’s hermeneutic views, according to which the task of the interpreter hermeneutist is to understand and interpret speech as an individual creative act.According to O. Potebnia’s hermeneutic research, the object of understanding is not only the author but also the artistic form created by him. The latter each time generates different sense at the level of the recipient in the process of perception – understanding – interpretation and contributes to different sense generation.